Postdigital disconnects : the discursive formation of technology in education - Mathier, Marion (New York : Routledge, 2023)
"This book employs a critical discourse ethnographic approach to map the production of social meaning in digital media in education, drawing on insights from Switzerland to unpack the disconnects which arise in thinking postdigitally and ways forward for rethinking sociocultural approaches. Grounded in Foucault-influenced, linguistically-oriented discourse studies, the book calls attention to the ways in which educational discourse has increasingly promoted digital media as a means of justifying curriculum change. Using data from policy documents, participant observation and interviews, Mathier charts how this rhetoric manifests itself in the combination of top-down policies, on-the-ground implementation, and the lived experiences of students outside the classroom, and in turn, surfaces broader disconnects. The volume explores how digital education is increasingly shaped by platform capitalism, how young people's experiences are disregarded in formal knowledge production, and how the prevalence of digital teaching and learning contributes to issues of access and inequality. Through a critical discursive approach, Mathier demonstrates the need for literacy practices in postdigital education to interrogate the ways in which digital media and education are entangled in lager sociopolitical practices. This book will appeal to students and scholars in critical discourse studies, critical literacy studies, digital communication, education research, and linguistic ethnography"--
Introduction: The Discursive Formation of Technology in Education -- Rebooting Education: Technology and Learning in (Swiss) Policy Discourse -- Machines, not Learners? An Event Ethnography of "Technologies for Teaching and Learning" -- "Between a Rock and a Hard Place?" Teachers' Discursive Constructions of Technological Change in the Classroom -- Wired Whizzes? Young People's Digital Media Practices Outside the Classroom -- "Just for fun?" Young People Articulating the Disconnects -- Conclusion: Postdigital Disconnects.
Keywords: Education and state -- Switzerland; Educational innovations -- Switzerland; Blended learning -- Switzerland; Computer-assisted instruction -- Switzerland; Creative teaching -- Switzerland; Students -- Effect of technological innovations on; Internet literacy -- Switzerland; Interdisciplinary approach in education; Education and globalization; Critical discourse analysis; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Linguistics